Pengaruh Ukuran Perusahaan dan Profitabilitas Terhadap Harga Saham yang Terdaftar di Bursa Efek Indonesia - Setiawati, Tiara Masri Dwiriski; Supeno, Wangsit (LPPM Universitas Bina Sarana Informatika, 2024)
Transportation is the process of transporting products and people from one location to another through machines and vehicles driven by humans. As part of the distribution chain of goods and passengers that grows every year, the transportation sector plays an important role in various domains such as politics, socio-culture, defense and security, especially in the economic sector. This study aims to examine the effect of Company Size and Profitability (ROA) on Stock Price. The sample in this study consisted of 8 transportation subsector companies listed on the Indonesia Stock Exchange that had met the criteria as research samples in the 2020-2023 period. The research method in thisresearch is descriptive research with a quantitative approach. Research on data in the form of Company financial facts obtained based on secondary data, namely data obtained in finished form. Based on the Multiple Regression Test and the results of the t test, it is found that the Company Sizevariable has a significant positive effect on stock prices, based on the results of the t test and Multiple Regression Test, that the ROA variable does not have a positive and significant effect on Stock Prices. Company Size and ROA simultaneously have a positive and significant impact on Stock Prices.